2018
DOI: 10.1093/geronb/gby047
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Analyses of the Trend in Poverty Among Older Adults: The Case of South Korea

Abstract: The Korean experience shows what would have happened to older adults in rich welfare states if mature old-age income security programs had not been in place. It may also provide some lessons for lower-income countries where poverty among older adults is set to become a larger problem in the coming decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…The results from the decomposition analyses suggest that contributions from older age groups to the observed inequalities became greater, implying that older adults can experience increasing burdens of economic deficiency and obesity-related health issues. Considering the rapid aging of the population and the disproportionately increasing rate of poverty among old adults in Korea [68], policy interventions need to be developed to facilitate weight control for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the decomposition analyses suggest that contributions from older age groups to the observed inequalities became greater, implying that older adults can experience increasing burdens of economic deficiency and obesity-related health issues. Considering the rapid aging of the population and the disproportionately increasing rate of poverty among old adults in Korea [68], policy interventions need to be developed to facilitate weight control for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by Australia (35.5%), Mexico (31.2%), the United States (21.5%), and Japan (19.4%), with the OECD average being 12.6% . Moreover, the poverty rate among older adults in Korea is approximately 3.5 times higher than the poverty rate of the remainder of the population (14.6%) …”
Section: Introductionmentioning
confidence: 98%
“…22 Moreover, the poverty rate among older adults in Korea is approximately 3.5 times higher than the poverty rate of the remainder of the population (14.6%). 23 Previous research has suggested that poorer senior citizens were more likely to suffer from mental illness, providing grounds for a direct association between poverty and suicide risk. [24][25][26][27][28] Thus, our study investigated the impact of poverty on suicide risk among older adults using a relatively large and nationally representative dataset.…”
mentioning
confidence: 99%
“…Old age, especially ≥70 years, was a critical factor for ID deaths in Korea, which could be attributed to biological susceptibility to IDs, but might also be ascribed to the socioeconomic vulnerability of the elderly. For instance, Korea's relative poverty rate (proportion of population with incomes below 50% of the median income) for the elderly has been around 45%, over three times higher than the OECD and national averages [21]. Among the elderly, the rate was even higher among those who were older, lived alone, female, and less educated [21].…”
Section: Discussionmentioning
confidence: 98%